Role of Human Resources Training in Building Leadership Administrative Abilities (Applied in Sahil & Sahara Bank (Headquarter), Republic of Chad) - Daifallah, AbuBakar Adam; Hassabo, Hassabo Ahmed (Journal of Economic, Administrative and Legal Sciences, 2024)
This study aimed at recognition of identifying the mechanisms of training needs for building the abilities of the administrative leaders in Sahel bank. The study problem revealing in the weak attention of training in financial institutions work force, which it has negative impact on the abilities of the leaders. The study hypothesized there is static significant between training of human resources & abilities building of the administrative leaders. The analytical descriptive & historical methods were used for collecting data from the respective sample and analyzed accordingly. The study concluded to various findings such as; the efficiency of the training needs relied on the efficiency of conducted training programs, the bank has fair training plans for improving the employees performance, also the researchers have suggested identifying training needs according to the current abilities of the employees to cope with banks modern activities, it is important to qualify & raise the abilities and skills of the employees to prepare them for future leadership jobs.